(untitled) (Eurasian Scientific Herald, 2022)
Qutbaddin al-Shirazi was widely known as an encyclopedic scientist. V.V. Barthold considered him "a great astronomer and physicist who was looking for new ways in science."One of the first historians of science who turned to the study of the scientific heritage of al-Shirazi was E. Wiedeman, who researched and partially translated into German the "Treatise on rolling motion and the relation between a plane and a curve" relating to geometric optics and the shape of the Earth "Shah’s gift in astronomy", The purpose of this work is to study and evaluate the scientific heritage of al-Shirazi in physics and astronomy, the formation of his scientific views, the influence on the scientific creativity of the scientist of the writings of his predecessors and the role of the scientific heritage of al-Shirazi in the work of subsequent scientists of the medieval Near and Middle East